Siblings On Artificial Intelligence: “It Is All About The Bottom Line, Period!” - Gupta, Divya; Gupta, Deepak (Indian Journal of Community Health, 2023)
It may appear to be a wordy jargon but moral compass, ethical compass and legal compass in artificial intelligence are nothing but about the bottom line and the bottom line is whether humans and their systems will co-exist with artificial intelligence or whether artificial intelligence will outlast (outlive) humans and their systems.